2002
DOI: 10.1054/jhsb.2002.0830
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study of the Dorsal Cutaneous Branches of the Digital Arteries

Abstract: This study describes the anatomy of the dorsal digital arteries in the 144 fingers of 18 pairs of fresh human cadaver hands. Previous studies have shown two constant branches in the proximal and middle pulp spaces from each proper digital artery. We have shown that these branches have consistent sites of origin at predictable distances from the proximal interphalangeal joint. Thus cutaneous flaps can be safely planned on these dorsal vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 5 publications
4
44
1
4
Order By: Relevance
“…Patients were excluded if they had (1) concomitant injuries to the dorsal or volar aspects of the proximal phalanx that precluded the use of the donor site, (2) injury to the course of the PDA and its second dorsal branch at the pedicle site, (3) active infection in the digit, and (4) no Doppler sound heard at the location of the second dorsal branch.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were excluded if they had (1) concomitant injuries to the dorsal or volar aspects of the proximal phalanx that precluded the use of the donor site, (2) injury to the course of the PDA and its second dorsal branch at the pedicle site, (3) active infection in the digit, and (4) no Doppler sound heard at the location of the second dorsal branch.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Braga-Silva et al [2] confirmed the existence of continuous vascular networks between the dorsal branches, which constitute the vascular system over the dorsum of a finger. At the proximal phalanx, the dorsal digital arteries stemmed from the dorsal metacarpal arteries anastomose with the vascular system ( Fig.…”
Section: Introductionmentioning
confidence: 92%
“…Anatomical studies demonstrated that the distribution of the dorsal branches of the digital artery is regular and repetitive in each phalanx [6,7]. Braga-Silva et al [8] found the existence of continuous vascular networks between the dorsal branches, which constituted the vascular system over the dorsum of the finger (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%